An Analysis of Students’ Reading Comprehension Difficulties during Covid-19 Pandemic with Online Classes in Junior High School - Hersagita Anissa Hayati; Nina Puspitaloka (Journal of English Teaching, 2022)
This study aimed at finding out the junior high school students' difficulties in reading and students' attempts to overcome their reading difficulties during the covid-19 pandemic. This study used a qualitative method with a descriptive approach. The research participant took from six students in junior high school in Karawang with different levels from high, middle, and high levels, each level took from two students. The data on students’ reading comprehension difficulties were collected through observation, interviews, and documentation. The results show that students’ reading comprehension difficulties were affected by internal factors and external factors. and the use of the internet became the media for students’ attempts to deal with reading difficulties.